SPE Europec/Eage Annual Conference 2012
DOI: 10.2118/154472-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Optimisation Algorithm for Inflow Control Valve Management

Abstract: Intelligent Wells are distinguished from conventional wells by being equipped with downhole sensors to monitor the Inflow Control Valves (ICVs) to control the (multiple) zonal flow rates. The data from the downhole sensors monitors the properties of the fluid flowing into the well from the reservoir at a zonal or a well level. The sensor data is analysed to provide the necessary information for the ICVs to be operated in the optimum manner i.e. to increase the hydrocarbon recovery and prevent unwanted fluid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The pump performance was forecast using a linear function of oil flowrate with respect to water cut between the initial conditions to a water cut of 80%. ( Grebenkin and Davies, 2012) introduced the concept of a zonal "critical water cut". This work showed that, for reactive optimisation, an ICV should be closed once the zone produces at a water cut greater than the "critical water cut" value.…”
Section: Esp Workflow Option A: Current Condition Design With Low Frementioning
confidence: 99%
See 2 more Smart Citations
“…The pump performance was forecast using a linear function of oil flowrate with respect to water cut between the initial conditions to a water cut of 80%. ( Grebenkin and Davies, 2012) introduced the concept of a zonal "critical water cut". This work showed that, for reactive optimisation, an ICV should be closed once the zone produces at a water cut greater than the "critical water cut" value.…”
Section: Esp Workflow Option A: Current Condition Design With Low Frementioning
confidence: 99%
“…This will be aided by the calculating the "critical water cut" value at which each (ICV) zone should be closed (Grebenkin and Davies, 2012). Unfortunately, we do not have the necessary information to carry out the full economic analysis described above; though we were able to prepare the qualitative comparison of Workflow A and B (Figures 14 and 15) by assuming that the water cut increases linearly with time.…”
Section: Design Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guyaguler and Byer (2008) used piecewise linear function with mixed-integer linear programming to provide an optimum reactive solution to the production-allocation problem in conventional wells. This approach improves the shortterm (current) objectives by optimizing this nonlinear equation subject to active constraints.…”
Section: Introductionmentioning
confidence: 99%
“…AICDs and AICVs are passive devices that are capable of actively control the unwanted fluid flow after breakthrough. ICVs are active devices with the capability of change the inflow area enabling the operator to control the well in a proactive and/or reactive manner (Kharghoria et al (2002), Yeten et al, 2004, Aitokhuehi and Durlofsky, 2005, Ebadi and Davies, 2006, Haghighat Sefat et al, 2013, Grebenkin and Davies, 2012, Addiego-Guevara et al, 2008.…”
Section: Introductionmentioning
confidence: 99%